Have crops already reached peak suitability: assessing global climatic suitability decreases for crop cultivation - Vhiny-Guilley Mombo; Mathilde Duvallet; Michiel Schaeffer; Florent Baarsch (Environmental Research Letters)
Crop yield and the availability of arable land are impacted by climate change, leading to effects on global patterns of production and trading. To gain more precise insights in how future climate change might lead to redistributing productive crop areas, we developed a new method to assess climatic crop suitability, which combines temperature and precipitation suitability through water balance calculations. We applied the method to evaluate the effects of climate change under two climatic scenarios (SSP2-4.5 and SSP5-8.5), using an ensemble of five general circulation models, for nine crops (Arabica coffee, cassava, common beans, common wheat, maize, plantain, rice, sorghum and sugarcane) for four periods of time: past (1995–2014), present day (2015–2034), medium term (2040–2059), long term (2080–2099). We observed that the fraction of area with optimal suitability might be on a downward trajectory for coffee, cassava, beans, wheat and plantain, and could be halved by the end of the century. The tropics and sub-tropics are negatively affected for all crops, while mid-latitudes see large decreases in suitability for beans, wheat and maize. Global patterns show that suitability decreases at local levels (in about 30% of the global area for bean and wheat) are not compensated by increases in suitability elsewhere (in about 19% of the area for bean and wheat). As relocation and expansion of production areas are constrained by available arable land, other strategies might be considered to improve suitability, such as irrigation, which would increase the area of optimal suitability from 5%–25% to 40%–50% of total arable land for the nine crops. Drainage could improve the optimal suitability area fivefold for maize and sorghum, while shading increases suitability for coffee (by up to 20% in both cases). The increased risk of food supply shortages led by climatic suitability loss may trigger increased deforestation if adaptation measures are not implemented.